The phenomenon of retronomy in neologisms (Texas Journal of Philology, Culture and History, 2024)
The article is introduced with considerations about the reasons that give rise to retronyms. In the following places, emphasis is placed on the issues of retronymy becoming a component of science and its inclusion in dictionaries, as well as processes related to neologisms. The retronymic series of words given as an example in the article consist of words from the Uzbek lexical layer. Also, retronyms and neologisms of the simple, compound and word combination type are shown with examples.